Clinico-radiological and functional outcome of Mayo type IIA olecranon fractures managed with tension band wiring in a tertiary care centre in North India - Spolia, Pankaj; Ghani, Abdul; Arfee, Sakib (International Journal of Research in Orthopaedics, 2021)
Background: Tension band wiring is the most common operative technique for the internal fixation of olecranon fractures. Stable internal fixation with figure of eight tension band wiring used for simple transverse fractures allows early range of motion, minimize stiffness and gives good results. The aim of this study is to evaluate the functional outcome of simple transverse fractures managed by tension band wiring. Methods: This was an observational prospective study of 24 patients with Mayo type IIA fractures aged between 18 to 65 years, with mean age of 42.5 years treated by tension band wiring. Functional outcome was assessed with Mayo Elbow Performance Score (MEPS) and Visual Analogue Scale (VAS) subjective pain score. Results: Our study was conducted on 24 patients with Mayo type IIA, out of which 16 were males and 8 were females. Most common mode of injury was fall from standing height (75%), followed by road traffic accident (16.7%) and assault (8.3%). The age range was between 18 to 65 years, with mean age of 42.5 years. Conclusions: Tension band wiring is an effective method for the treatment of transverse, non-comminuted and unstable fractures of the olecranon which provides stable fixation, early rehabilitation and gives excellent results when done in expert hands.